High-speed algorithm for carrier frequency recovery and frame synchronization in QPSK-modulated modems - A. V. Sadchenko; O. A. Kushnirenko; E. K. Koshelev; V. I. Bondar (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
When demodulating signals in communication systems with QPSK modulation operating in the pulsed mode, the following problems arise: rapid elimination of the reference oscillator phase ambiguity and ensuring reliable frame synchronization for a given noise immunity. In most QPSK modems, the carrier frequency recovery and synchronization recovery tasks are separated and solved with the help of different functional modules, which is not the optimal solution from the point of view of increasing the energy efficiency.